2008
DOI: 10.1007/s12253-008-9028-x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Tumour as Initial Manifestation of Acute Myeloid Leukemia: Granulocytic Sarcoma: Case Report

Abstract: We report orbital involvement as an initial manifestation of acute myeloid leukemia in a 57-year-old woman. The patient presented with painful proptosis and limited ocular motility. Orbital computed tomography revealed bilateral homogeneous masses. Orbital biopsy was performed on the right side; and histopathology disclosed a myelocytic tumour. Despite treatment using irradiation and chemotherapy, the patient died eleven months after presentation. There appear to be only a few previous reports of acute myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Notably, none of the paediatric patients with primary orbital manifestations had leukaemic infiltrates in the retina or choroid, whereas four of six patients with secondary ophthalmic leukaemias had such infiltrates. Taken together, our findings further emphasise the broad clinical spectrum of leukaemic lesions that may manifest in the eye or ocular region,1 3 4 6 7 10 11 and the need to consider leukaemia in the differential diagnosis of patients with proptosis, reduced mobility and/or displacement of the eye 1 4 6…”
Section: Discussionmentioning
confidence: 52%
“…Notably, none of the paediatric patients with primary orbital manifestations had leukaemic infiltrates in the retina or choroid, whereas four of six patients with secondary ophthalmic leukaemias had such infiltrates. Taken together, our findings further emphasise the broad clinical spectrum of leukaemic lesions that may manifest in the eye or ocular region,1 3 4 6 7 10 11 and the need to consider leukaemia in the differential diagnosis of patients with proptosis, reduced mobility and/or displacement of the eye 1 4 6…”
Section: Discussionmentioning
confidence: 52%
“…15 The common characteristics of orbital MS were proptosis, chemosis, orbital mass, and lid edema. 14 , 16 , 17 Ocular MS in adult AML patients was 10 out of 3,724 (0.3%) in the study, 17 whereas Cavdar et al reported 33 orbito-ocular MS in 133 Turkish children with AML. 18 The Children’s Oncology Group concluded that patients with MS involving orbital and central nervous system (CNS) sites had significantly better survival than patients with non-CNS MS, with CSF leukemia, or without extramedullary leukemia.…”
Section: Discussionmentioning
confidence: 62%
“…The direct infiltration of the orbits in leukemia can present with proptosis, chemosis, lid edema, intra‑retinal macular or sub‑hyaloid hemorrhages, cotton wool spots, blurring of vision, diplopia, palsies of the extra‑ocular muscle, or papilledema due to the increased intracranial pressure 5. Most cases of orbital involvement in AML present with unilateral proptosis,7–11 and few case reports have reported bilateral orbital involvement as an initial manifestation of AML 12,13…”
Section: Discussionmentioning
confidence: 99%